Farnesysltransferase Inhibitor Prevents Burn Injury-Induced Metabolome Changes in Muscle - Harumasa Nakazawa; Lai Ping Wong; Laura Shelton; Ruslan Sadreyev; Masao Kaneki (Metabolites, 2022)
Burn injury remains a significant public health issue worldwide. Metabolic derangements are a major complication of burn injury and negatively affect the clinical outcomes of severely burned patients. These metabolic aberrations include muscle wasting, hypermetabolism, hyperglycemia, hyperlactatemia, insulin resistance, and mitochondrial dysfunction. However, little is known about the impact of burn injury on the metabolome profile in skeletal muscle. We have previously shown that farnesyltransferase inhibitor (FTI) reverses burn injury-induced insulin resistance, mitochondrial dysfunction, and the Warburg effect in mouse skeletal muscle. To evaluate metabolome composition, targeted quantitative analysis was performed using capillary electrophoresis mass spectrometry in mouse skeletal muscle. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), and hierarchical cluster analysis demonstrated that burn injury induced a global change in metabolome composition. FTI treatment almost completely prevented burn injury-induced alterations in metabolite levels. Pathway analysis revealed that the pathways most affected by burn injury were purine, glutathione, β-alanine, glycine, serine, and threonine metabolism. Burn injury induced a suppressed oxidized to reduced nicotinamide adenine dinucleotide (NAD+/NADH) ratio as well as oxidative stress and adenosine triphosphate (ATP) depletion, all of which were reversed by FTI. Moreover, our data raise the possibility that burn injury may lead to increased glutaminolysis and reductive carboxylation in mouse skeletal muscle.